Estudo fitoquímico do extrato hexânico e da atividade biológica de constituintes das folhas de Maytenus robusta (Celastraceae) - Grasiely Faria de Sousa (2012)
Phytochemical study of the hexane extract from the leaves of M. robustaand of the solid obtained during the preparation of this extract resulted in the isolation of seven pentacyclic triterpenes: 3-oxofriedelane, 3b-hydroxyfriedelane, 3-oxo-11b-hydroxyfriedelane, 3-oxo-29-hydroxyfriedelane, 3b,11b-dihydroxyfriedelane,3-oxo-21b-H-hop-22(29)-ene and 3b-hydroxy-21b-H-hop-22(29)-ene. The triterpenes with seco-friedelan skeleton, 3,4-seco-friedelan-3,11b-olide and 3,4-seco-friedelan-3-oic acid, the triterpene with seco-hopene skeleton, 3,4-seco-21b-H-hop-22(29)-en-3-oic acid, the steroid sitosterol, mixtures of long chain hydrocarbons, the sesqueterpene 2,6,11-trimethyldodeca-2,6,10-triene and the long chain fatty acid hentriacontanoic acid were also isolated. The chemicalstructures were determined by spectroscopic methods (IR, 1H and 13C NMR, HSQC, HMBC and NOESY). The triterpenes 3b,11b-dihydroxyfriedelane and 3,4-seco-friedelan-3,11b-olide are new compounds. The study of the biological activity consisted of antimicrobial activity, activity of the capacity to inhibit acetylcholinesterase and evaluation of toxic potential through larvicidal activity on Artemia salina. The triterpenes 3b,11b-dihydroxyfriedelane and 3b-hydroxy-21b-H-hop-22(29)-ene showed cholinesteraseinhibiting activities. This activity was also observed for the chloroform, ethyl acetate and methanol extracts. The solid obtained during the preparation of chloroform extract was active against S. aureus, C. albicans and B. cereus. The ethyl acetate extract showed activity against B. cereus, S. typhimurium, S. aureus and C. albicans. The solid obtained during the preparation of hexane extract showed activity against C. albicans.